Influence of Ag Doping on the Microstructural, Optical, and Electrical Properties of ZrSiN Coatings Deposited through Pulsed-DC Reactive Magnetron Sputtering - Vanegas Parra, Henry Samir (2023)
The functional properties of the transition-metal nitride coatings can be modified by adding noble metals such as silver. The incorporation of these elements has been demonstrated to be a good strategy for improving the electrical, optical, and mechanical responses of transition-metal nitride coatings. In this investigation, we report the production of Ag-ZrSiN coatings with varying silver atomic contents, deposited using pulsed-DC reactive magnetron sputtering. The effect of the incorporation of silver on the microstructure, the morphology, and the optical and electrical properties was investigated. The results revealed a nanocomposite structure of Ag-ZrSiN with nc-Ag/nc-ZrN embedded in an amorphous SiNx phase. The electrical resistivity decreased upon the incorporation of Ag from 77.99 W cm to 0.71 W cm for 0.0 and 12.0 at.% of Ag, respectively. A similar decreasing trend was observed in the transmittance spectra of the coatings as the silver content increased. For the Ag-ZrSiN coating, the transmittance values decreased within the wavelength range of 2500–630 nm and then remained constant down to 300 nm, at about 13.7%. Upon further increase of the silver concentration up to 12 at.%, the transmittance values continued to decrease between 2500 and 630 nm, reaching approximately zero at 630 nm, indicating that the coating becomes opaque within that spectral range.